The bioenergetics of inflammation: insights into obesity and type 2 diabetes - Keane, Kevin; Calton, E.; Carlessi, Rodrigo; Hart, P.; Newsholme, Philip (Nature Publishing Group, 2017)
Diabetes mellitus is one of the most common chronic metabolic disorders worldwide, and its incidence in Asian countries is alarmingly high. Type 2 diabetes (T2DM) is closely associated with obesity, and the staggering rise in obesity is one of the primary factors related to the increased frequency of T2DM. Low-grade chronic inflammation is also accepted as an integral metabolic adaption in obesity and T2DM, and is believed to be a major player in the onset of insulin resistance. However, the exact mechanism(s) that cause a persistent chronic low-grade infiltration of leukocytes into insulin-target tissues such as adipose, skeletal muscle and liver are not entirely known. Recent developments in the understanding of leukocyte metabolism have revealed that the inflammatory polarization of immune cells, and consequently their immunological function, are strongly connected to their metabolic profile. Therefore, it is hypothesized that dysfunctional immune cell metabolism is a central cellular mechanism that prevents the resolution of inflammation in chronic metabolic conditions such as that observed in obesity and T2DM. The purpose of this review is to explore the metabolic demands of different immune cell types, and identify the molecular switches that control immune cell metabolism and ultimately function. Understanding of these concepts may allow the development of interventions that can correct immune function and may possibly decrease chronic low-grade inflammation in humans suffering from obesity and T2DM. We also review the latest clinical techniques used to measure metabolic flux in primary leukocytes isolated from obese and T2DM patients.European Journal of Clinical Nutrition advance online publication, 12 April 2017; doi:10.1038/ejcn.2017.45.